Acute effects of temperature and hypercarbia on cutaneous and branchial gas exchange in the South American lungfish, Lepidosiren paradoxa - Zena, Lucas A. [UNESP]; Bicego, Kenia C. [UNESP]; Silva, Glauber S. F. da [UNESP]; Giusti, Humberto; Glass, Mogens L.; Sanchez, Adriana P. (Elsevier B.V., 2017)
The South American lungfish, Lepidosiren paradoxa inhabits seasonal environments in the Central Amazon and Parana-Paraguay basins that undergo significant oscillations in temperature throughout the year. They rely on different gas exchange organs, such as gills and skin for aquatic gas exchange while their truly bilateral lungs are responsible for aerial gas exchange; however, there are no data available on the individual contributions of the skin and the gills to total aquatic gas exchange in L. paradoxa. Thus, in the present study we quantify the relative contributions of skin and gills on total aquatic gas exchange during warm (35 degrees C) and cold exposure (20 degrees C) in addition to the effects of aerial and aquatic hypercarbia on aquatic gas exchange and gill ventilation rate (f(G); 25 degrees C), respectively. Elevated temperature (35 degrees C) caused a significant increase in the contribution of cutaneous (from 0.61 +/- 0.13 to 1.34 +/- 0.26 ml. STPD.h(-1) kg(-1)) and branchial (from 0.54 +/- 0.17 to 1.73 +/- 0.53 ml. STPD.h(-1) kg(-1)) gas exchange for (V) over dotCO(2) relative to the lower temperature (20 degrees C), while (V) over dot O-2 remained relatively unchanged. L. paradoxa exhibited a greater branchial contribution in relation to total aquatic gas exchange at lower temperatures (20 and 25 degrees C) for oxygen uptake. Aerial hypercarbia decreased branchial (V) over dot O-2 whereas branchial (V) over dotCO(2) was significantly increased. Progressive increases in aquatic hypercarbia did not affect f(G). This response is in contrast to increases in pulmonary ventilation that may offset any increase in arterial partial pressure of CO2 owing to CO2 loading through the animals' branchial surface. Thus, despite their reduced contribution to total gas exchange, cutaneous and branchial gas exchange in L. paradoxa can be significantly affected by temperature and aerial hypercarbia.
Keywords: Lungfish; O-2 uptake; CO2 elimination; Dipnoi